ANALYZING SOCIAL NETWORKS: IDENTIFYING TRENDS AND USER CLUSTERS - Aizhan Adilkhan (Modern American Journals, 2025)
Social media has undoubtedly become one of the major sources of information and information interaction in the modern world. As billions of users communicate daily on platforms such as TikTok, Facebook, Instagram, Twitter, etc., the problems of detecting trends and hidden structure of these networks have both scientific and practical significance. This paper discusses the critical aspects of community detection, methodologies, algorithms and tools used today, as well as the real-world impact and future prospects of this interesting research area.
Keywords: Social network analysis; online community; clustering method; data clustering; graph model; online communities; features of cluster analysis.